Cost-Effective Utilization of Agricultural Waste for the Production of Industrially Important Enzymes by Aspergillus Niger (Journal of Asian Development Studies, 2025)
To overcome the environmental and sustainability challenges caused by agro-wastes, such as wheat straw (Triticum aestivum L.), wheat bran (Triticum aestivum L.), and rice husk (Oryza sativa L.) biotechnological innovations played a vital role. This research focused on the use of lignocellulolytic fungus Aspergillus niger in solid-state fermentation for the cost-effective production of cellulase and pectinase enzymes with agricultural residues as substrates. The evaluation of wheat bran as a substrate for fungal growth revealed the highest fungal cellulase activity and pectinase activity at 6.47 ± 0.35 U/g and 4.03 ± 0.25 U/g, respectively. Wheat bran outperformed other substrates in terms of cellulose and pectinase activity, hence strengthening its position as a fermentation substrate. Moderate enzyme production was shown by rice husk (cellulase activity 3.27 ± 0.25 U/g and pectinase activity 1.90 ± 0.20 U/g). Wheat straw showed the least enzyme activity (1.03 ± 0.15 U/g cellulase and 0.73 ± 0.15 U/g pectinase), likely because high-cellulose fibrous materials slow down enzymatic breakdown of complex structures. These results showed the potential of agro-residues and agro-industrial waste, particularly wheat bran, as substrates for controlled bioprocesses, for the advancement of sustainable byproduct enzyme production and eco-friendly workflows.